Pengaruh Pinjaman Online sebagai Faktor Pemicu Terjadinya Perceraian: Studi Kasus Nomor 243/Pdt.G/2025/PA.CN - Dewi Purnama, Arianne Kania; Hudoyo , Asti Al Syahrani; Zulfani , Sakiya; Faturahman , Dadan Taufik (Universitas Sains dan Teknologi Komputer, 2025)
Divorce is the official termination of the marriage relationship between husband and wife, which results in the two no longer being bound as husband and wife. The divorce process usually involves a court decision and the existence of valid reasons according to the law. The results show that online lending is not the main reason for divorce according to the applicable legal provisions. However, honest behavior in debt, ignoring the obligation to pay off debts, and husband's inability to fulfill maintenance are the dominant factors that trigger conflict in the household. The burden of unresolved debts, intimidating collection methods, and the dissemination of personal data by online loan service providers contribute to psychological pressure and embarrassment, which ultimately worsen relations between spouses. In case Number 243/Pdt.G/ 2025/PA.CN , the Compilation of Islamic Law, which stipulates that divorce can be granted if there is continuous disagreement and quarrel between husband and wife without hope of getting back together.